2011
DOI: 10.1590/s0004-28032011000200002
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial lung disease and gastroesophageal reflux disease: key role of esophageal function tests in the diagnosis and treatment

Abstract: -Context -Gastroesophageal reflux disease (GERD) is common in patients with respiratory disorders and interstitial lung fibrosis from diverse disease processes. However, a cause-effect relationship has not been well demonstrated. It is hypothesized that there might be more than a coincidental association between GERD and interstitial lung damage. There is still confusion about the diagnostic steps necessary to confirm the presence of GERD, and about the role of effective control of GERD in the natural history … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 27 publications
2
25
0
2
Order By: Relevance
“…The prevalence of abnormal GER was reported in 23 studies [4,10,26,27,48,75,79,80,[101][102][103][104][105][106][107][108][109][110][111][112][113][114][115] (online supplementary table S6) and ranged from 0 among 20 IPF patients in Ireland who were participating in a study exploring the degree and mechanisms of sleep-disordered breathing, and for whom no history of GER was noted [80], to 94.1% in an analysis of consecutive, newly diagnosed IPF patients recruited from a single US centre [112] (figure 6). However, the 94% prevalence was based on a 24-h ambulatory physiological definition of abnormal acid GER: a most sensitive method of ascertaining abnormal acid GER that included abnormal acid exposure in the distal and/or proximal oesophagus.…”
Section: Nonrespiratory Comorbidities Gastro-oesophageal Reflux Diseasementioning
confidence: 99%
“…The prevalence of abnormal GER was reported in 23 studies [4,10,26,27,48,75,79,80,[101][102][103][104][105][106][107][108][109][110][111][112][113][114][115] (online supplementary table S6) and ranged from 0 among 20 IPF patients in Ireland who were participating in a study exploring the degree and mechanisms of sleep-disordered breathing, and for whom no history of GER was noted [80], to 94.1% in an analysis of consecutive, newly diagnosed IPF patients recruited from a single US centre [112] (figure 6). However, the 94% prevalence was based on a 24-h ambulatory physiological definition of abnormal acid GER: a most sensitive method of ascertaining abnormal acid GER that included abnormal acid exposure in the distal and/or proximal oesophagus.…”
Section: Nonrespiratory Comorbidities Gastro-oesophageal Reflux Diseasementioning
confidence: 99%
“…[1][2][3] In particular, many studies have reported the higher prevalence of GERD in IPF. [4][5][6][7][8][9][10][11][12][13] The prevalence of GERD in patients with IPF was reportedly 67 to 88% in Western populations, [8][9][10]12,13 and 62.3% (43 of 69 patients) in China. 6 Although the mechanism is unclear, chronic microaspiration due to GERD has been considered to be one of the causes of IPF through repeated subclinical injury to the lungs.…”
Section: Introductionmentioning
confidence: 99%
“…Esophageal dysfunction in patients with systemic sclerosis or other lung diseases is seldom detected at early stage (Ing 2001;Raghu 2003;Gaude 2009;Christmann et al 2010;Soares et al 2011), probably because reflux disease is often clinically silent (Raghu 2003) and diagnostic tests such as manometry, pH and impedance monitoring, endoscopy, and scintigraphy, are invasive or not routinely performed in everyday practice. Using CT scan measurements has several advantages in assessing esophageal dysfunction over the conventional methods.…”
Section: Discussionmentioning
confidence: 99%